Matematyka

Autorzy:Janowicz Jerzy

Wydawnictwo:Nowa Era

Rok wydania:2015

Wykonaj mnożenie i przeprowadź redukcję wyrazów podobnych 4.0 gwiazdek na podstawie 7 opinii
  1. Gimnazjum
  2. 1 Klasa
  3. Matematyka

Wykonaj mnożenie i przeprowadź redukcję wyrazów podobnych

30
 Zadanie
31
 Zadanie
32
 Zadanie

33
 Zadanie

34
 Zadanie

`a)\ (5x+2)(3x+1)(2x+3)=` 

`\ \ \ =[5x(3x+1)+2(3x+1)](2x+3)=` 

` \ \ \ =[15x^2+5x+6x+2](2x+3)=` 

`\ \ \ =(15x^2+11x+2)(2x+3)=` 

`\ \ \ =(15x^2+11x+2)*2x+(15x^2+11x+2)*3=` 

`\ \ \ =30x^3+22x^2+4x+45x^2+33x+6=` 

`\ \ \ =30x^3+67x^2+37x+6` 

 

`b)\ (9x^2+3x)(5x-1)(2x^2+1)=` 

`\ \ \ =[9x^2(5x-1)+3x(5x-1)](2x^2+1)=` 

`\ \ \ =[45x^3-9x^2+15x^2-3x](2x^2+1)=`

`\ \ \ =[45x^3+6x^2-3x](2x^2+1)=` 

`\ \ \ =(45x^3+6x^2-3x)*2x^2+(45x^3+6x^2-3x)*1=` 

`\ \ \ =90x^5+12x^4-6x^3+45x^3+6x^2-3x=` 

`\ \ \ =90x^5+12x^4+39x^3+6x^2-3x` 

 

`c)\ (p+q)(p-q)(p^2+q^2)=` 

`\ \ \ =(p^2-q^2)(p^2+q^2)=` 

`\ \ \ =(p^2)^2-(q^2)^2=p^4-q^4` 

 

`d)\ (0,2xy^2-1)(0,5x^2y+1)(x+y)=` 

`\ \ \ =[0,2xy^2(0,5x^2y+1)-1(0,5x^2y+1)](x+y)=` 

`\ \ \ =[0,1x^3y^3+0,2xy^2-0,5x^2y-1](x+y)=`  

`\ \ \ =(0,1x^3y^3+0,2xy^2-0,5x^2y-1)*x+(0,1x^3y^3+0,2xy^2-0,5x^2y-1)*y=`     

`\ \ \ =0,1x^4y^3+0,2x^2y^2-0,5x^3y-x+0,1x^3y^4+0,2xy^3-0,5x^2y^2-y=`   

`\ \ \ =0,1x^4y^3+0,1x^3y^4-0,5x^3y-0,3x^2y^2+0,2xy^3-y`